Resposta do feijoeiro "Rico 23" à aplicação de enxofre, boro e molibdênio - Mário Braga, José (Revista Ceres, 2025)
The application of boron, molybdenum and sulphur was made in a Red Yellow Podzolic Cambic soil, in Viçosa, Minas Gerais, in order to study the response of comnion bean. These elements were applie in the form of borax, sodium molybdate and gypsum, respectively.